Spatio-Temporal Patterns of Joshua Tree Stand Structure and Regeneration Following Mojave Desert Wildfires - St. Clair, Seth B.; St. Clair, Elijah A.; St. Clair, Samuel B. (Frontiers in Ecology and Evolution, 2022)
Joshua tree (Yucca brevifolia Englm.) plays a central role in the ecology of the Mojave Desert ecosystem. However, the emergence of invasive grass fire-cycles in the last several decades brings into question Joshua trees' tolerance and resilience to changing fire regimes. This study's objective was to examine the effects of wildfires on the structure and regeneration potential of Joshua trees forests. We examined the density, size class structure, and regeneration response of Joshua tree populations on a network of one kilometer transects along the boundaries of four independent wildfires and the interior of the largest fire that occurred fifteen years ago (2005) in the northeast Mojave Desert. Burned edge and burned interior transects had 23- and 4.1-fold lower Joshua tree stand densities than unburned transects. The more robust recovery of stand density along burned interior transects than burned edge transects appears to be primarily driven by more prolific vegetative sprouting. Our data show that Joshua trees can sprout vegetatively following fire, but it is not a strong or consistent post-fire resprouter. Limiting the spread of invasive annual grasses and novel fire regimes will be critical to maintaining healthy Joshua tree populations into the future, particularly on the edge of its ecological range.